N-Acetylcysteine Counteracts Immune Dysfunction and Autism-Related Behaviors in the Shank3b Mouse Model of Autism Spectrum Disorder - Luca Pangrazzi; Enrica Cerilli; Luigi Balasco; Ginevra Matilde Dall'O'; Gabriele Chelini; Anna Pastore; Birgit Weinberger; Yuri Bozzi (MDPI AG, 2024)
Autism spectrum disorder (ASD) includes a range of neurodevelopmental disabilities characterized by social interaction deficits, communication impairments, and repetitive behaviors. Previous studies have shown that pro-inflammatory conditions play a key role in ASD. Despite this, how oxidative stress and inflammation may contribute to ASD-related behaviors is still poorly understood. Here, we reported that increased levels of molecules related to inflammation are present in the cerebellum and peripheral blood (PB) of mice lacking Shank3b, an established model of syndromic ASD. In parallel, immune dysfunction was documented in the bone marrow (BM) and spleens of mutant mice. N-acetylcysteine (NAC) treatment rescued inflammation in the cerebellum and PB and impaired the production of pro-inflammatory molecules in the BM and spleen. In addition, social impairment was counteracted in NAC-treated Shank3b−/− animals. Taken together, our results provide clear evidence of the key role of cerebellar oxidative stress and inflammation in the establishment of ASD-related behaviors. Furthermore, our findings underscore the importance of considering ASD as a systemic disorder.